1995
DOI: 10.1126/science.7660130
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the von Hippel-Lindau Tumor Suppressor Protein to Elongin B and C

Abstract: Germ-line mutations of the von Hippel-Lindau tumor suppressor gene (VHL) predispose individuals to a variety of human tumors, and somatic mutations of this gene have been identified in sporadic renal cell carcinomas and cerebellar hemangioblastomas. Two transcriptional elongation factors, Elongin B and C, were shown to bind in vitro and in vivo to a short, colinear region of the VHL protein (pVHL) that is frequently mutated in human tumors. A peptide replica of this region inhibited binding of pVHL to Elongin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
456
1
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 626 publications
(474 citation statements)
references
References 19 publications
10
456
1
7
Order By: Relevance
“…The importance of gene expression being regulated at the level of transcriptional elongation was recently highlighted in studies demonstrating that the product of the von HippelLindau (VHL) tumour suppressor gene negatively regulates the elongation factor elongin (SIII). These studies found that mutations in the VHL protein interfered with this regulatory mechanism and led to a failure to regulate transcription at the level of elongation which thereby predisposed cells of the eye, kidney and central nervous system to carcinogenesis (Duan et al, 1995;Kibel et al, 1995;Aso et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of gene expression being regulated at the level of transcriptional elongation was recently highlighted in studies demonstrating that the product of the von HippelLindau (VHL) tumour suppressor gene negatively regulates the elongation factor elongin (SIII). These studies found that mutations in the VHL protein interfered with this regulatory mechanism and led to a failure to regulate transcription at the level of elongation which thereby predisposed cells of the eye, kidney and central nervous system to carcinogenesis (Duan et al, 1995;Kibel et al, 1995;Aso et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…d-VHL has an overall 22% identity to h-VHL and is 50% similar when conserved amino acid changes were considered ( Figure 1b). In the two functionally signiĀ®cant protein interaction domains, human residues 113 Ā± 121 and 157 Ā± 172 that encompass the protein kinase Cl (PKCl) and the elongin C binding sites, respectively (Okuda et al, 1999;Kibel et al, 1995), the conservation is signiĀ®cantly higher at 67 and 76%.…”
Section: Cloning Of the D-vhl Gene Sequencementioning
confidence: 99%
“…They consist of an oxygen-sensitive a-subunit and a constitutively expressed b-subunit, also known as ARNT or HIF-b. pVHL associates with the elongins B and C, cullin2 and Rbx [8][9][10][11][12] and functions as the substrate recognition component of an E3-ubiquitin ligase that ubiquitylates HIF-a. [13][14][15][16][17][18][19] All three HIF a-subunits, HIF-1a, HIF-2a and HIF-3a interact with pVHL.…”
mentioning
confidence: 99%